Strengthening of the Lower House of Representatives: Case Compared to Argentina - Rincón-Suescún, Geisson Santiago (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this research arises, based on the constitutional democratic principle, the need to increase the number of members of the Colombian Lower House of Representatives, and with this purpose it is compared to the Lower House of Argentina. It also explores how the election of representatives has changedsince the entry into force of the 1991 Constitution, with shows that with the change in the form of the election of this House it was given more participation to minority parties.